320-Row Multidetector Computed Tomographic Angiogram in the Evaluation of Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage. Issue 4 (July 2015) - Hébert, Julien; Roncarolo, Federico; Tampieri, Donatella; Cortes, Maria delPilar
<x xml:space="preserve">Abstract</x> Objective To objectively assess the accuracy of 320-row multidetector computed tomographic (CT) angiography to diagnose cerebral vasospasm after a subarachnoid hemorrhage using a new quantitative method. Methods Fifty-four arterial segments were measured in 8 patients who had subarachnoid hemorrhage and underwent digital subtraction angiography within 24 hours after CT angiography for clinical suspicion of cerebral vasospasm. Results A correlation between arterial diameters measurements made on CT angiography and digital subtraction angiography was observed. The degree of vasospasm tended to be overestimated in the anterior circulation, with arterial diameters that were between 0.05 and 0.72 mm smaller than those on digital subtraction angiography. Conclusions A quantitative approach can be used to objectively evaluate the ability of multidetector CT angiography to assess arterial diameter in patients with clinical symptoms of postsubarachnoid hemorrhage cerebral vasospasm. This pilot study also suggests that CT angiography may overestimate the degree of cerebral vasospasm in the anterior circulation.